Targeting the carbohydrates on HIV-1: Interaction of oligomannose dendrons with human monoclonal antibody 2G12 and DC-SIGN - Wang, Sheng-Kai; Liang, Pi-Hui; Astronomo, Rena D; Hsu, Tsui-Ling; Hsieh, Shie-Liang; Burton, Dennis R; Wong, Chi-Huey (Proceedings of the National Academy of Sciences - PNAS, 2008)
It is widely accepted that the heavily glycosylated glycoprotein gp120 on the surface of HIV-1 shields peptide epitopes from recognition by the immune system and may promote infection in vivo by interaction with dendritic cells and transport to tissue rich in CD4⁺ T cells such as lymph nodes. A conserved cluster of oligomannose glycans on gp120 has been identified as the epitope recognized by the broadly HIV-1-neutralizing monoclonal antibody 2G12. Oligomannose glycans are also the ligands for DC-SIGN, a C-type lectin found on the surface of dendritic cells. Multivalency is fundamental for carbohydrate-protein interactions, and mimicking of the high glycan density on the virus surface has become essential for designing carbohydrate-based HIV vaccines and antiviral agents. We report an efficient synthesis of oligomannose dendrons, which display multivalent oligomannoses in high density, and characterize their interaction with 2G12 and DC-SIGN by a glycan microarray binding assay. The solution and the surface binding analysis of 2G12 to a prototype oligomannose dendron clearly demonstrated the efficacy of dendrimeric display. We further showed that these glycodendrons inhibit the binding of gp120 to 2G12 and recombinant dimeric DC-SIGN with IC₅₀ in the nanomolar range. A second-generation Man₉ dendron was identified as a potential immunogen for HIV vaccine development and as a potential antiviral agent.